Assessment of Panoramic Radiographic Variables as Predictors of Inferior Alveolar Nerve Injury During Third Molar Extraction - Lubna Shaukat; Zafar Ali Khan; Rakhi Issrani; Naseer Ahmed; Muhtada Ahmad; Farrukh Abu Hazim; Namdeo Prabhu (Association of Support to Oral Health Research (APESB), 2023)
Objective: To assess the role of radiological predictive markers on orthopantomogram for inferior alveolar nerve (IAN) injury related to the removal of mandibular third molar surgery and the occurrence of post-operative IAN paresthesia. Material and Methods: This prospective observational study was conducted on 60 patients (aged 17-35 years) indicated for extraction and showed one or more of the seven previously known panoramic radiographic risk signs of IAN injury. Variables such as age, sex, tooth angulation, and relationship with the inferior alveolar canal (IAC) were assessed to see their outcome on IAN injury. Data analysis is presented through tables and descriptive methods. Results: Among patients, 26 were male and 34 were female, with a mean age of 26.17 years. Out of seven radiological predictive markers, only six were found in this study, whereas one marker, viz. interruption of white line of the canal was not found. After surgical removal of the lower third molar, only two patients with radiographic signs showing the deflection of roots and darkening of roots continued with sensory deficit 5 weeks post-operatively. Conclusion: The risk of inferior alveolar nerve injury during lower third molar surgery is very low, even in patients with radiological predictive markers.